Factors associated with dengue hemorrhagic fever protection behavior in Thailand: literature review - Sangkuy, Tanunya; Woradet, Somkiattiyos; Chaimay, Bhunyabhadh (UBRU Journal for Public Health Research, 2020)
Dengue hemorrhagic fever is vector borne disease which has an outbreak continuously. It remains a major health problem worldwide. The disease prevention and control are needed strictly and continuously in order to reduce the transmission of diseases. In addition, it needs to be participated by public and civil sectors, in particular, the disease prevention and control behavior in individuals. The objective of this article aimed to review literature related to factors associated with dengue hemorrhagic fever protection behavior. The research articles published in national databases were reviewed by PRECEDE Model conceptual framework. It shows that personal factors (sex, age, marital status, education level, occupation, duration of community residence, history of illness, income and social status), predisposing factors (attitude, knowledge and perception), enabling factors (resource sufficiency) and reinforcing factors (social supports, receiving advices from health professionals and receiving motivation) were associated with dengue hemorrhagic fever protection behavior. From mentioned those factors, health professionals in both public and civil sectors should promote protection behavior, disseminate dengue hemorrhagic fever, support resource and empower in dengue hemorrhagic fever protection behavior in order to lead the appropriate and the right of dengue hemorrhagic fever protection behavior.